Forensic study on rural road pavement failures along Parit Sumarto - Jelani, Jestin (2006)
Road deformation was occurred so prevalent on rural roads of Batu Pahat vicinity moreover when it's constructed on soft ground. This study presents the results of forensic investigation of a deterioration portion of the Parit Sumarto rural road. This road had been selected as represent of most common types of road deterioration found in Batu Pahat vicinity through field survey conducted for month in August, 2006. The deformation occurred at the right side of the road which located adjacent to the open drain. No deformation seen at the opposed side. The deterioration mechanism hypotheses may due to inadequate layer thicknesses and inappropriate geometry conditions. Extensive field and laboratory testing was conductect to verify the hypotheses. Field investigation was initiated by nondestructive testing (NDT) like ground penetrating radar (GPR) to observe pavement layer thickness and subsurface condition. Mini falling weight deflectometer (MFWD) measure the modulus of the unbound layer and lastly density gauge (DG) for density measurement. Subsequently destructive testing (DT) like dynamic cone penetrometer (DCP) for assessment of unbound layer and thickness determination was conducted. Also, coring and trenching to obtain samples for further laboratory tests. Two locations were trench; one at deteriorated section and one were outside the deteriorated location. MFWD results in this study revealed unsatisfactory as they are significant low. Layer thickness determination via GPR, DCP and trenching was at acceptable differences. The data obtained from NDTs, DTs and laboratory were than used in 2D finite element method (Plaxis) and multilayer elastic analysis (Kenlayer). By using Plaxis in this study, it is found that the root cause of the deformation was inappropriate geometrical design pertaining to road shoulder width. Meanwhile, Kennlayer analysis had shown that apparent differences in road layer thicknesses seem to be a contribution factor in deformation. In this study, evaluation of instrumentations used is also discussed to determine its suitability and effectiveness.